Analysis of The Influence of Environmental, Social, and Governance (Esg) on Financial Performance: An Empirical Study of LQ45 Companies on The Indonesia Stock Exchange Period 2023-2025 - Chandra; Surya Raharja (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the influence of Environmental (E), Social (S), and Governance (G) on corporate financial performance as measured by Return on Assets (ROA) and Return on Invested Capital (ROIC) in companies listed on the LQ45 index of the Indonesia Stock Exchange for the 2023-2025 period, with Company Size (SIZE) as a control variable. The study uses a quantitative method with secondary data obtained from annual reports and corporate sustainability reports. The sample was determined using a purposive sampling technique, resulting in 45 observations included in the LQ45 for the 2023-2025 period. Data analysis was performed using panel data regression with the help of EViews 13 software. The results show that Environmental has a positive and significant effect on ROA and ROIC, while Governance also has a positive and significant effect on both indicators. Conversely, Social does not have a significant effect on ROA or ROIC. The coefficient of determination value indicates that the model is able to explain variations in ROA by 29.7% and ROIC by 32.3%. These findings indicate that environmental practices and corporate governance play an important role in improving financial performance, while the implementation of social aspects has not had a significant impact during the study period.